![\displaystyle\lim_{h\to0}\frac{\tan\sqrt{x+h}-\tan x}h](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bh%5Cto0%7D%5Cfrac%7B%5Ctan%5Csqrt%7Bx%2Bh%7D-%5Ctan%20x%7Dh)
Employ a standard trick used in proving the chain rule:
![\dfrac{\tan\sqrt{x+h}-\tan x}{\sqrt{x+h}-\sqrt x}\cdot\dfrac{\sqrt{x+h}-\sqrt x}h](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Ctan%5Csqrt%7Bx%2Bh%7D-%5Ctan%20x%7D%7B%5Csqrt%7Bx%2Bh%7D-%5Csqrt%20x%7D%5Ccdot%5Cdfrac%7B%5Csqrt%7Bx%2Bh%7D-%5Csqrt%20x%7Dh)
The limit of a product is the product of limits, i.e. we can write
![\displaystyle\left(\lim_{h\to0}\frac{\tan\sqrt{x+h}-\tan x}{\sqrt{x+h}-\sqrt x}\right)\cdot\left(\lim_{h\to0}\frac{\sqrt{x+h}-\sqrt x}h\right)](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cleft%28%5Clim_%7Bh%5Cto0%7D%5Cfrac%7B%5Ctan%5Csqrt%7Bx%2Bh%7D-%5Ctan%20x%7D%7B%5Csqrt%7Bx%2Bh%7D-%5Csqrt%20x%7D%5Cright%29%5Ccdot%5Cleft%28%5Clim_%7Bh%5Cto0%7D%5Cfrac%7B%5Csqrt%7Bx%2Bh%7D-%5Csqrt%20x%7Dh%5Cright%29)
The rightmost limit is an exercise in differentiating
![\sqrt x](https://tex.z-dn.net/?f=%5Csqrt%20x)
using the definition, which you probably already know is
![\dfrac1{2\sqrt x}](https://tex.z-dn.net/?f=%5Cdfrac1%7B2%5Csqrt%20x%7D)
.
For the leftmost limit, we make a substitution
![y=\sqrt x](https://tex.z-dn.net/?f=y%3D%5Csqrt%20x)
. Now, if we make a slight change to
![x](https://tex.z-dn.net/?f=x)
by adding a small number
![h](https://tex.z-dn.net/?f=h)
, this propagates a similar small change in
![y](https://tex.z-dn.net/?f=y)
that we'll call
![h'](https://tex.z-dn.net/?f=h%27)
, so that we can set
![y+h'=\sqrt{x+h}](https://tex.z-dn.net/?f=y%2Bh%27%3D%5Csqrt%7Bx%2Bh%7D)
. Then as
![h\to0](https://tex.z-dn.net/?f=h%5Cto0)
, we see that it's also the case that
![h'\to0](https://tex.z-dn.net/?f=h%27%5Cto0)
(since we fix
![y=\sqrt x](https://tex.z-dn.net/?f=y%3D%5Csqrt%20x)
). So we can write the remaining limit as
![\displaystyle\lim_{h\to0}\frac{\tan\sqrt{x+h}-\tan\sqrt x}{\sqrt{x+h}-\sqrt x}=\lim_{h'\to0}\frac{\tan(y+h')-\tan y}{y+h'-y}=\lim_{h'\to0}\frac{\tan(y+h')-\tan y}{h'}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bh%5Cto0%7D%5Cfrac%7B%5Ctan%5Csqrt%7Bx%2Bh%7D-%5Ctan%5Csqrt%20x%7D%7B%5Csqrt%7Bx%2Bh%7D-%5Csqrt%20x%7D%3D%5Clim_%7Bh%27%5Cto0%7D%5Cfrac%7B%5Ctan%28y%2Bh%27%29-%5Ctan%20y%7D%7By%2Bh%27-y%7D%3D%5Clim_%7Bh%27%5Cto0%7D%5Cfrac%7B%5Ctan%28y%2Bh%27%29-%5Ctan%20y%7D%7Bh%27%7D)
which in turn is the derivative of
![\tan y](https://tex.z-dn.net/?f=%5Ctan%20y)
, another limit you probably already know how to compute. We'd end up with
![\sec^2y](https://tex.z-dn.net/?f=%5Csec%5E2y)
, or
![\sec^2\sqrt x](https://tex.z-dn.net/?f=%5Csec%5E2%5Csqrt%20x)
.
So we find that